PENGARUH PENDEKATAN ETNOPEDAGOGI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS SISWA DI SD NEGERI PANTON LUAS BARU - YUSRIZAL . (JURNAL ILMIAH MAKSITEK, 2020)
This research aims to: (1) Know the difference in students' IPS learning outcomes taught with an ethnopedagogi approachcompared to conventional approaches; (2) Knowing the difference in students' IPS learning results that have high motivationcompared to low motivation; (3) Know the interaction between learning approach and learning motivation in influencingstudents' IPS learning outcomes. This research was conducted at SD Negeri Panton Luas Baru Samadua District SouthAceh Regency. The sample in this study was 50 grade IV students. Data collection techniques through motivational learningquestionnaires and IPS learning test instruments. This type of research is a pseudo-experiment with a 2 x 2 factorial design,while hypothetical testing is conducted with a two-way ANAVA. The results showed that: (1) Students' IPS learning outcomestaught with an ethnopedagogi approach were higher than those taught with conventional approaches (Fhitung = 23,476 andsig. 0.000 > 0.05); (2) The results of studying ips students who are highly motivated are higher than those with low motivation(Fhitung = 7,673 and sig. 0.008 > 0.05); (3) There is an interaction between the learning approach and the motivation oflearning in influencing the student's IPS learning outcomes (Fhitung = 13,003 and sig. 0.001 > 0.05).